Unravelling the New Plebiscitary Democracy: Towards a Research Agenda. Issue 4 (20th October 2021) - Hendriks, Frank
Abstract: Pushed by technological, cultural and related political drivers, a 'new plebiscitary democracy' is emerging which challenges established electoral democracy as well as variants of deliberative democracy. The new plebiscitary democracy reinvents and radicalizes longer-existing methods (initiative, referendum, recall, primary, petition, poll) with new tools and applications (mostly digital). It comes with a comparatively thin conceptualization of democracy, invoking the bare notion of a demos whose aggregated will is to steer actors and issues in public governance in a straight majoritarian way. In addition to unravelling the reinvented logic of plebiscitary democracy in conceptual terms, this article fleshes out an empirically informed matrix of emerging formats, distinguishing between votations that are 'political-leader' and 'public-issue' oriented on the one hand, and 'inside-out' and 'outside-in' initiated on the other hand. Relatedly, it proposes an agenda for systematic research into the various guises, drivers and implications of the new plebiscitary democracy. Finally, it reflects on possible objections to the argumentation.